Impact of Maximal Transurethral Resection on Pathological Outcomes at Cystectomy in a Large, Multi-institutional Cohort. Issue 5 (16th May 2023) - Kirk, Peter S.; Lotan, Yair; Zargar, Homayoun; Fairey, Adrian S.; Dinney, Colin P.; Mir, Maria C.; Krabbe, Laura-Maria; Cookson, Michael S.; Jacobson, Niels-Erik; Montgomery, Jeffrey S.; Vasdev, Nikhil; Yu, Evan Y.; et al.
Abstract : Purpose: While the presence of residual disease at the time of radical cystectomy for bladder cancer is an established prognostic indicator, controversy remains regarding the importance of maximal transurethral resection prior to neoadjuvant chemotherapy. We characterized the influence of maximal transurethral resection on pathological and survival outcomes using a large, multi-institutional cohort. Materials and Methods: We identified 785 patients from a multi-institutional cohort undergoing radical cystectomy for muscle-invasive bladder cancer after neoadjuvant chemotherapy. We employed bivariate comparisons and stratified multivariable models to quantify the effect of maximal transurethral resection on pathological findings at cystectomy and survival. Results: Of 785 patients, 579 (74%) underwent maximal transurethral resection. Incomplete transurethral resection was more frequent in patients with more advanced clinical tumor (cT) and nodal (cN) stage ( P < .001 and P < .01, respectively), with more advanced ypT stage at cystectomy and higher rates of positive surgical margins ( P < .01 and P < .05, respectively). In multivariable models, maximal transurethral resection was associated with downstaging at cystectomy (adjusted odds ratio 1.6, 95% CI 1.1-2.5). In Cox proportional hazards analysis, maximal transurethral resection was not associated with overall survival (adjusted HR 0.8, 95% CI 0.6-1.1). Conclusions: In patients undergoing transurethral resection for muscle-invasive bladder cancer prior to neoadjuvant chemotherapy, maximal resection may improve pathological response at cystectomy. However, the ultimate effects on long-term survival and oncologic outcomes warrant further investigation.